Antifungal Activity, Mode of Action, Docking Prediction and Anti-biofilm Effects of (+)-β-pinene Enantiomers against Candida spp. - de Macêdo Andrade, Ana Cláudia; Rosalen, Pedro L.; Freires, Irlan Almeida; Scotti, Luciana; Scotti, Marcus Tulius; Aquino, Sabrina Garcia; de Castro, Ricardo Dias (Current Topics in Medicinal Chemistry, 2018)
Aims: The objective of this study was to investigate the effectiveness of (+)-β-pinene inhibition on Candida spp. growth, aiming at elucidation of the mechanism of action; to determine fungal cell enzyme binding activity (through molecular docking simulations) and its effects on biofilm reduction. Methods: Candida strains (n=25) from referenced and clinical origins, either susceptible or resistant to standard clinical antifungals, were tested for determination of Minimum Inhibitory Concentration (MIC); Minimum Fungicidal Concentration (MFC); and microbial death curves upon treatment with (+)-β-pinene; the effects of (+)-β-pinene on the cell wall (sorbitol assay), membrane ergosterol binding, and effects on biofilm were evaluated by microdilution techniques. We also evaluated the interactions between (+)-β-pinene and cell wall and membrane enzymes of interest. Results: The MIC values of (+)-β-pinene ranged from <56.25 to 1800 μmol/L. The MIC of (+)-β-pinene did not increase when ergosterol was added to the medium, however it did increase in the presence of sorbitol, leading to a doubled MIC for C. tropicalis and C. krusei. The results of the molecular docking simulations indicated better interaction with delta-14-sterol reductase (−51 kcal/mol). (+)-β-pinene presents anti-biofilm activity against multiples species of Candida. Conclusion: (+)-β-pinene has antifungal activity and most likely acts through interference with the cell wall; through molecular interaction with Delta-14-sterol reductase and, to a lesser extent, with the 1,3-β- glucan synthase. This molecule was also found to effectively reduce Candida biofilm adhesion.
Keywords: Products with antimicrobial action